2014
DOI: 10.1371/journal.pone.0113906
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Middle Ear Ventilation Disorders: Sheep as Animal Model for Stenting the Human Eustachian Tube – A Cadaver Study

Abstract: Eustachian tube disorders can lead to chronic otitis media with consecutive conductive hearing loss. To improve treatment and to develop new types of implants such as stents, an adequate experimental animal model is required. As the middle ear of sheep is known to be comparable to the human middle ear, the dimensions of the Eustachian tube in two strains of sheep were investigated. The Eustachian tube and middle ear of half heads of heathland and blackface sheep were filled with silicone rubber, blended with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
(26 reference statements)
1
24
0
1
Order By: Relevance
“…However, Miller et al . reported that the ET curvature of blackface sheep had an angle of 162.4° and decreased from the pharyngeal orifice to the tympanic orifice (Miller et al ., ). The ET of the miniature pig was approximately the same shape as that of the sheep, but it had a completely different course.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Miller et al . reported that the ET curvature of blackface sheep had an angle of 162.4° and decreased from the pharyngeal orifice to the tympanic orifice (Miller et al ., ). The ET of the miniature pig was approximately the same shape as that of the sheep, but it had a completely different course.…”
Section: Discussionmentioning
confidence: 97%
“…Miller et al . () used a silicone model to evaluate the dimensions of the ET. This method is suitable for studying a cavity or tube, and we used this approach in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, a permanent stent or temporary scaffold shall be applied for the restoration of the physiological venting function of the Eustashian tube, mediated by anti-inflammatory and antiinfective local drug release [16].…”
Section: Otolaryngologic Implantsmentioning
confidence: 99%
“…However, the success rate could not be confirmed in a following study [65]. Currently tube stents are developed to improve the tube function with transpharyngeal insertion [77]. In first investigations with sheep, chrome cobalt coronary stents (ProKinetic Energy) (Figure 13 (Fig.…”
Section: Evidence Gapsmentioning
confidence: 99%